The Management of Corporate Financial Assets: Applications of Mathematical Programming Models (Book). - Onsi, Mohamed (The Accounting Review, 1988)
Reviews the book "The Management of Corporate Financial Assets: Applications of Mathematical Programming Models," by J.S.H. Kornbluth and G.R. Salkin.